From need to action: decoding the role of motivation in adherence to home-based cardiac rehabilitation exercise in chronic heart failure patients - Zhen Yang; Hao Huang; Linyu Xu; Yu Gao; Chunqi Zhang; Aiping Wang (BMC Nursing)
Abstract Background Adherence to home-based cardiac rehabilitation exercise remains suboptimal, and motivation may be the intrinsic driving force. This study aimed to explore the role of exercise regulatory motivation in mediating the relationship between psychological needs and exercise adherence among chronic heart failure patients, and to develop a mechanism model. Methods This study adopted an explanatory sequential mixed-methods design. A hypothesized model of adherence behavior was developed. A survey was used to test the theory-driven model. A semi-structured interview delved deeper into chronic heart failure patients’ experiences with HBCR exercise, identifying reasons behind significant mediation effects and refining the mechanism model. Results A total of 248 eligible chronic heart failure patients participated in the quantitative study. Exercise regulatory motivation partially mediated the relationship between psychological needs and exercise adherence. In the qualitative study, 18 chronic heart failure patients from the quantitative sample were purposefully selected. Five sub-themes emerged from the textual data, which were distilled into two overarching themes: “Specific Functions of Pathway Variables” and “Reasons for Mediation Path Significance.” Integrating the qualitative and quantitative results, it was found that satisfying patients’ psychological needs for exercise activates regulatory motivation, which in turn triggers sustained exercise behavior. As motivation becomes increasingly internalized, patients are able to set clear goals and maintain or adjust their home-based cardiac rehabilitation exercise over the long term. Conclusion From a health psychology perspective, this study is the first to reveal the role of exercise regulatory motivation in linking psychological needs and exercise adherence among chronic heart failure patients, ultimately developing a mechanism model. Clinical Trial Number Not applicable.